The Israeli-Palestinian conflict : the struggle for Middle East peace - Orr, Tamra (World history (Lucent Press), 2020)
Traces the history of the Israeli-Palestinian conflict in the Middle East, describing key people, battles, meetings, and developments. Includes sidebars, a timeline, photographs, primary sources, and further resources.